Building and validating an educational video for elderly individuals about fall risks - Guilherme Guarino de Moura Sá; Ana Maria Ribeiro dos Santos; Nelson Miguel Galindo Neto; Khelyane Mesquita de Carvalho; Carla Danielle Araújo Feitosa; Polyana Norberta Mendes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to build and validate educational video for elderly individuals about fall risks. Methods: methodological study with video building. validated by 22 judges and assessed by 22 elderly individuals. Content was selected from the Fall Prevention Model and items from the Falls Risk Awareness Questionnaire. Items with an agreement greater than 0.80 were considered valid. verified through Content Validation Index (CVI) and binomial test. Results: building the video was guided by the Cognitive Theory of Multimedia Learning. Digital animation and audio narration were used. It lasted ten minutes and five seconds and included biological. socioeconomic. behavioral and environmental risks as well as precautions to avoid them. The CVI of judges had an average of 0.99. and of elderly individuals. an average of 1.0. Conclusion: the video was built and validated for content and understanding and can be used to prevent falls in elderly individuals.